Kinematic Analysis of Wrist and Elbow Angles in Badminton Serve Techniques Based on IMU Sensors - Larasaty, Perwita Aura; Laksono, Pringgo Widyo; Suhardi, Bambang (Applied Research in Science and Technology, 2025)
Background: Motion capture technology is essential in sports biomechanics for analyzing human movement. Inertial Measurement Unit (IMU) sensors offer a practical alternative to camera-based systems, providing real-time motion analysis. While previous studies in badminton biomechanics have largely focused on stroke phases or lower-limb movements using optical systems, few have investigated the detailed angular behavior of upper-limb joint-particularly the wrist and forearm during specific serve types. Moreover, existing research rarely compares different serve techniques in terms of kinematics using wearable IMU-based methods.Aims: This study aims to analyze angular movement patterns of the wrist and forearm during different badminton serve techniques using IMU sensor. Understanding the wrist and forearm movements is crucial, as they directly affect shuttle control, serve conssitency, and injury risk- especiaally in high-spedd, repetitive motions like the badminton serve.Methods: Sensors were placed on the dorsum of the hand and the forearm near elbow to measure angular motion in three serves: backhand, short forehand, and long forehand.Result: Results indicate that the centroid calculation results showed that each type of serves had a different angular distribution pattern, with varying contributions from the forearm and wrist. The forearm plays a dominant role in generating power, while the wrist contributes more to directional control and stabilization. Results indicate that forearm movement is more dominant in forehand serves, while wrist movement is more pronounced in backhand serves. These findings suggest that IMU-based motion analysis can optimize badminton techniques, prevent injuries, and enhance training programs.